Evaluating vehicle trafficability on soft ground using wheel force information - Mingming Liu; Longlong Chen; Yanxi Ren (Measurement + Control)
In the areas of aerospace and military industry, wheeled vehicles are expected to have the ability of passing various ground surfaces, including lunar soil, sand, marsh, mud flat, etc. This makes vehicle trafficability on soft ground become a very hot research topic. There are very a few difficulties in the present research of vehicle trafficability on soft ground, such as obtaining wheel-ground interaction information, inaccurate identification of soil mechanical characteristics parameters, and single evaluation index. In this paper, a novel approach of evaluating the vehicle trafficability on soft ground using wheel force information is proposed. As parts of the proposed approach, the methods of obtaining wheel force information, identification of soil mechanical characteristics parameters and integated method of trafficability evaluation, are discussed in detail. The proposed approach was validated through a practical test.